Ambiguous authority and hidden hierarchy: Collective leadership in an elite professional service firm. (February 2020) - Empson, Laura
This study represents a detailed analysis of collective leadership in an elite professional service firm, examining the distinctive power dynamics revealed among professional peers as they attempt to act decisively in response to an acute organizational crisis. It identifies how professional peers deliberately construct and amplify ambiguity in both the composition and authority of their collective leadership group, and examines how that ambiguity can serve a functional purpose for group members. Intuitive mutual adjustment is the prevailing pattern of interaction, but this changes to a more managed form of mutual adjustment as a hidden hierarchy is revealed in response to the crisis. The study identifies the micro interactions which constitute both intuitive and managed mutual adjustment, and shows how members of a collective leadership group can maintain cohesion and act decisively, in spite of lacking the formal authority to do so. The findings challenge some foundational assumptions of collective leadership theory and extend our understanding of leadership power dynamics more generally by demonstrating how leaders can exercise considerable informal power under the cloak of ambiguity, highlighting the hidden hierarchy that can exist within a collective, and emphasizing the significance of individual 'heroic' leader within collective leadership.